Connectivity in the Virtual Office Space: Catalyst or Impediment to TMT Agility? - Scarlat, Elvira; Neacsu, Ionela; M. Elvira, Marta; Rodríguez-Lluesma, Carlos (Springer, 2022)
In today’s fast-paced and uncertain business landscape, coping with technology developments, increased demand for innovative products, and competitive shifts require top management teams (TMTs) to respond to these challenges with increasingly higher levels of agility. Given the recent rise of ICT in business communication, in this conceptual paper we build on the attention-based view of the firm to shed light on the impact of ICT in shaping the TMT agility. We discuss how ICT can either enhance or impair TMT agility, and identify TMT- and firm-level contingencies that boost the interplay between the two concepts.
Keywords: TMT agility; Information technology; Communication technologies; Decision-making